Profiling Croatian Whisky Using GC/MS-MS and UHPLC-QTOF - Ante Lončarić; Aly Castillo; Maria Celeiro; Borislav Miličević; Hrvoje Bušić; Tomo Anadolac; Ana-Marija Gotal Skoko; Marta Lores (Applied Sciences)
This study investigates the chemical profiling of Croatian whisky using advanced analytical techniques: Solid-phase microextraction followed by gas chromatography coupled to mass spectrometry (SPME-GC-MS) and ultra-high-performance liquid chromatography quadrupole time-of-flight (UHPLC-QTOF). To our knowledge, there are no studies on profiling Croatian whiskies to date. Therefore, the primary objective is to identify and quantify the volatile and non-volatile compounds contributing to the flavor and aroma profile of Croatian whisky. The methods applied included sample preparation, extraction, and subsequent analysis using these advanced analytical techniques. The results revealed a diverse range of compounds, including esters, alcohols, phenols, and acids, which are integral to the whisky’s sensory characteristics. Furthermore, key volatile and non-volatile compounds were identified in Croatian whiskies, revealing a complex aromatic profile influenced by compounds like D-limonene, linalool, and β-damascenone, which contribute citrus, floral, and fruity notes. The findings also highlighted compounds associated with aging, such as esculetin and ellagic acid, which enhance flavor complexity and emphasized the role of maturation, grain type, and production methods in shaping the unique sensory characteristics of Croatian whiskies. This study concludes that SPME-GC-MS and UHPLC-QTOF are effective tools for the detailed chemical profiling of whisky, providing valuable insights for quality control and product differentiation in the whisky industry.